THE INFLUENCE OF BANKING CORPORATE SOCIAL RESPONSIBILITY (CSR) THROUGH FINANCIAL PERFORMANCE - Sri Suryaningsum; Indra Kusumawardhani; Rizki Andriani; Muhammad Irhas Effendi; Raden Hendri Gusaptono (University of Merdeka Malang, 2016)
This study aims to determine the influence of corporate social responsibility (CSR) which had been focusing proxy components to the environment, energy, health and safety, labor, product, public health and the financial performance using the variable return on equity (ROE). The sample was taken by 10 banking companies which listed on the Stock Exchange in the year 2007 to 2012 revealing the CSR in the annual report. T he sampling method technique used purposive sampling. The model used in this research is multiple linear regressions. The results showing the influence of CSR simultaneously was measured by components of the environment, energy, health and safety, labor, product, public health and the return on equity (ROE) relating to F counted as equal to 6.522 with a significance level of 0.000 and the environment variable partially that did not affect the ROE as a significance level of 0.881 0.05, thus energy variables did not significantly ROE due to the significance 0.980 0.05. The other variables concerning to the health and safety of workers significant influence with ROE due to the significance of 0.002 0.05. In addition, the other variables of labor has not significant ROE due to the significance 0.683 0.05, variable product does not influence significant the ROE because of the significance 0.490 0.05, variable community involvement did not influence significantly the ROE is due to the significance 0.234 0.05 and a common variable influence significantly the ROE for significance 0.002 0.05.